False Summit: Gender in Mountaineering Nonfiction. By Julie Rak (Montreal: McGill-Queen's University Press, 2021), 268pp. - Peter Hansen (Journal of the Austrian Association for American Studies, 2021)
This is a review of Julie Rak's monograph False Summit (2021).